2020
DOI: 10.1080/13102818.2020.1809520
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of microsatellites associated with resistance against bacterial leaf blight and blast diseases of rice (Oryza sativa L.)

Abstract: Bacterial leaf blight (BLB) and blast are among the most destructive diseases of rice. In order to develop new varieties that can resist various races of the pathogens Xanthomonas oryzae pv. oryzae (Xoo) and Magnaporthe oryzae, which cause these two diseases, respectively, it is important to identify suitable markers and a marker-aided selection strategy. Seventeen foreground microsatellites associated with resistance against BLB and blast were screened for polymorphism for possible adoption in a breeding prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Our results met the expectations based on common genetic knowledge. Similar data were reported for rice, wheat, and maize 39 41 . As a side effect, our results demonstrate the accurateness of hand crosses because we found no self-pollination events.…”
Section: Discussionsupporting
confidence: 86%
“…Our results met the expectations based on common genetic knowledge. Similar data were reported for rice, wheat, and maize 39 41 . As a side effect, our results demonstrate the accurateness of hand crosses because we found no self-pollination events.…”
Section: Discussionsupporting
confidence: 86%
“…The current study tested five sets of molecular markers that had previously shown functional polymorphisms for each of the target traits, including Wx -SSR, fgr -SNP, pTA248, RM8225, and RM202 [ 19 , 20 , 21 , 22 , 23 , 24 ]. All of the selected markers showed functional polymorphisms with expected sizes of amplified products ( Table 5 ), indicating that they can be employed for multiplexing.…”
Section: Resultsmentioning
confidence: 99%
“…Genes such as Ammonium transport (AMT), nitrate transport (NRT), glutamine synthetase (GS), and glutamate synthase (GOGAT) play pivotal roles in nitrogen metabolism. Studies have demonstrated that transgenic crops overexpressing these genes exhibit elevated tissue nitrogen levels, increased amino acids, and enhanced biomass and greater seed production (Curatti and Rubio, 2014). For instance, the gene OsDREB1C, responsible for promoting nitrogen use efficiency and resource allocation while shortening growth, has led to a substantial increase in rice yield, ranging from 41.3% to 68.3% compared to wild types when overexpressed (Wei et al, 2022).…”
Section: Enhancing Physiological Efficiency Of Plantsmentioning
confidence: 99%